Zwitterionic BODIPYs with large stokes shift: small molecular biomarkers for live cells. Issue 6 (5th January 2017) - Sekhar, Adiki Raja; Sariki, Santhosh Kumar; Reddy, R. V. Ramana; Bisai, Alakesh; Sahu, Pushpendra Kumar; Tomar, Raghuvir S.; Sankar, Jeyaraman
Abstract : Two novel first examples of zwitterionic BODIPYs have been identified as promising imaging agents for granules inside live yeast cells. Abstract : The two first examples of zwitterionic BODIPYs have been synthesized via a simple SN -Ar methodology. The molecules exhibit excellent optical behavior, such as a large Stokes shift in solution and therefore a very intense emission, and can thus avoid self-quenching. The zwitterionic nature of the molecules was unambiguously elucidated using single crystal XRD studies. The electronic conjugation was investigated by NMR, DFT (NICS (0)) and XRD analysis. Due to their inherent ionic nature, their enhanced solubility in aqueous conditions was exploited for their utility in bio-imaging and cell viability studies. These molecules demonstrate promising localization inside live yeast cells.